Mixed Boundary Value Problems of a Transversely Isotropic Layer Under Torsion and Various Boundary Conditions - Rogowski, B. (Engineering Transactions, 1983)
This paper deals with the axially symmetric torsion of a transversely isotropic layer elastically supported at the lower plane or bonded with dissimilar half-space. Two types of the three-part mixed boundary value problems are considered: flat annular crack problem and annular torsional indentation problem. Numerical results are discussed and displayed graphically.